X-ray photoelectron spectroscopy analysis of whole cells and isolated cell walls of gram-positive bacteria: comparison with biochemical analysis - Dufrêne, Y F; van der Wal, A; Norde, W; Rouxhet, P G (Journal of Bacteriology, 1997)
Article Usage Stats Services JB Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JB About JB Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JB RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0021-9193 Online ISSN: 1098-5530 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JB .asm.org, visit: JB